2005
DOI: 10.1074/jbc.m410375200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Caldesmon on the Position and Myosin-induced Movement of Smooth Muscle Tropomyosin Bound to Actin

Abstract: It is known that the actin-binding protein caldesmon inhibits actomyosin ATPase activity and might in this way take part in the thin filament regulation of smooth muscle contraction. Although the molecular mechanism of this inhibition is unknown, it is clear that the presence of actin-bound tropomyosin is necessary for full inhibition. Recent evidence also suggests that the myosin-induced movement of tropomyosin plays a key role in regulation. In this work, fluorescence studies provide evidence to show that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…Förster resonance energy transfer (FRET) has widely been used for studies of TM dynamics on the thin filament [Tao et al, 1983;Miki, 1990;Graceffa, 1999Graceffa, , 2000Bacchiocchi and Lehrer, 2002;Bacchiocchi et al, 2004;Graceffa and Mazurkie, 2005]. In this work, we used this method to analyze the effect of isoform-specific sequences on localization of TM molecules on the actin filament.…”
mentioning
confidence: 96%
“…Förster resonance energy transfer (FRET) has widely been used for studies of TM dynamics on the thin filament [Tao et al, 1983;Miki, 1990;Graceffa, 1999Graceffa, , 2000Bacchiocchi and Lehrer, 2002;Bacchiocchi et al, 2004;Graceffa and Mazurkie, 2005]. In this work, we used this method to analyze the effect of isoform-specific sequences on localization of TM molecules on the actin filament.…”
mentioning
confidence: 96%
“…Tm has been described as a gatekeeper, regulating the access of actin to actin-binding proteins (11,18). This concept is likely to apply to smooth muscle as well (10,26). The fact that Tm1 associates predominately with ␥-actin at the cell cortex, whereas Tm6 is located at ␣/␤-actin stress fibers, points to a model where Tm variants, as gatekeepers of actin subpopulations, might differentially control the access of different actin-binding proteins, thereby also defining different functional cellular actin compartments.…”
Section: Discussionmentioning
confidence: 99%
“…It was subsequently found to be ubiquitous in smooth muscle, associated with thinfilaments in smooth muscle [Mabuchi et al, 1993;Fraser and Marston, 1995] and in nonmuscle cells, associated with actin microfilaments [Bretscher, 1986;Bryan, 1990;Matsumura and Yamashiro, 1993]. Further studies, showed that CaD binds to other smooth muscle contractile [Wang and Chacko, 1996;Wang et al, 1997a,b;El-Mezgueldi et al, 1998;Huber et al, 1998;Wang, 2001] and regulatory proteins Chacko, 1988, 1989;Watson et al, 1990;Horiuchi et al, 1995;Graceffa and Mazurkie, 2005]. Thus, CaD has been thought as an integral component of the thin filaments of the contractile apparatus of smooth muscle [Marston and Lehman, 1985;Furst et al, 1986].…”
Section: Introductionmentioning
confidence: 91%